How Maxone Engganges its Customer to be Loyal - widodo, teguh (Jurnal Manajemen dan Keuangan, 2024)
The purpose of this study is to determine the Effect of Customer engagement on Customer Loyalty with Customer Satisfaction as an Intervening Variable, study on Customers at Maxone Malang Hotel. Since in Malang City, many hotels have been established, and Maxone must be able to survive to maintain its customers so that they do not move to other hotels. The method used in this study is quantitative. The sampling number is 97 customers by implementing purposive sampling technique. Data collection was obtained through questionnaires distributed to Maxone customer. The collected data is processed with multiple linear analysis regression and sobel tests . Since this study show that customer enggagement affects customer satisfaction, customer enggagement affects customer loyalty, customer satisfaction affects customer loyalty and customer enggagement affects customer loyalty through customer satisfaction. It needs to enhance the enggagement for the customer to be loyal as implication.